PENGEMBANGAN MEDIA PEMBELAJARAN HISTORY WHEEL PADA MATERI PEMBENTUKAN NEGARA DAN PEMERINTAHAN REPUBLIK INDONESIA DALAM PEMBELAJARAN SEJARAH KELAS XII - Medita Dwiga; Zulfa Zulfa; Liza Husnita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the use of conventional learning media that rely solely on textbooks, which are not well suited to the visual and multitasking mindsets of today's students. This situation has resulted in low student achievement in history learning. The research question is how to develop the history wheel learning media for the material on the Formation of the State and Government of the Republic of Indonesia, including the Global and National Conditions leading up to Independence, the Formation of the BPUPKI, the Nine-Person Committee, and the Jakarta Charter (June 1945), the Proclamation of Independence, the PPKI Session, and the Formation of the BKR/TKR and Initial Institutions in class XII C2 of SMA N 12 Bungo. The method used is research and development (R&D) with the 4-D model (define, design, development, disseminate). The research subjects consisted of 23 students in class XII C2 of SMA N 12 Bungo. The research results showed: (1) the validation test obtained an average score of 89.8% with the category “very valid”, covering media feasibility aspects 86.7%, material feasibility 92%, and language feasibility 90.8%; (2) the practicality test for teachers obtained a score of 42 with a percentage of 93.3% in the “very practical” category; (3) student responses achieved a score of 1142 with a percentage of 90.28% in the “very practical” category. The conclusion of this study is that the development of the history wheel learning media is deemed highly valid and highly practical based on validation by media experts, content experts, language experts, as well as the results of practicality tests conducted by teachers and students. Therefore, the history wheel is effective as an innovative learning media for history education.